Rescue from replication stress during mitosis - Fragkos, Michalis (Cell Cycle, 2017)
Genomic instability is a hallmark of cancer and a common feature of human disorders, characterized by growth defects, neurodegeneration, cancer predisposition, and aging. Recent evidence has shown that DNA replication stress is a major driver of genomic instability and tumorigenesis. Cells can undergo mitosis with under-replicated DNA or unresolved DNA structures, and specific pathways are dedicated to resolving these structures during mitosis, suggesting that mitotic rescue from replication stress (MRRS) is a key process influencing genome stability and cellular homeostasis. Deregulation of MRRS following oncogene activation or loss-of-function of caretaker genes may be the cause of chromosomal aberrations that promote cancer initiation and progression. In this review, we discuss the causes and consequences of replication stress, focusing on its persistence in mitosis as well as the mechanisms and factors involved in its resolution, and the potential impact of incomplete replication or aberrant MRRS on tumorigenesis, aging and disease.